Legal aspects of military and diplomatic action khan little horde Abulhair (Journal of actual problems of jurisprudence, 2019)
This article describes the era of the Little Horde Khan Abulhair. And also sets out the political and military relationshipwith the neighboring countries.Key words: military-diplomatic actions, military-political position, military qualities, diplomacy power, politicalchoice.